Evaluation of Design Thinking in Logistics Management: A Case Study of the Double Diamond Method at PT Jamu Jago Semarang - Hartana, Aditya Pramana; Retnowati (International Journal Software Engineering and Computer Science (IJSECS), 2024)
In the era of globalization and increasing competition, an efficient logistics management system is crucial to ensuring the smooth operation of a company. PT Jamu Jago Semarang, a leading herbal medicine company in Indonesia established in 1918, faces challenges in managing production data, which is still handled semi-manually. This process often leads to recording errors and inaccuracies in inventory information regarding commodities and raw materials. To address these issues, this study recommends the adoption of the Design Thinking approach and the Double Diamond method to enhance the company's competitiveness and operational efficiency. The design of the logistics management system, based on Design Thinking and the Double Diamond method, resulted in a website prototype developed through the stages of Discover, Define, Develop, and Deliver. This prototype was subsequently evaluated using the User Experience Questionnaire (UEQ), which yielded high scores in the aspects of attractiveness, clarity, efficiency, accuracy, stimulation, and novelty, indicating the design's success in meeting user needs effectively